The Effect of Cold and Hot Executive Functions, Personality, General Intelligence and Emotional Intelligence in Transformational Leadership - Karatosidi, Chrysovalanto Sofia; Iordanoglou, Dimitra (Journal of Leadership, Accountability and Ethics, 2024)
This study investigates the role of hot and cold executive functions (EF) in transformational leadership, considering the mediating role of personality, general cognitive ability, and trait emotional intelligence (EI). EF plays an essential role in responding and adapting to new situations. The sample (N=316) consisted of students and leaders. Neuropsychological tests assessing specific domains of EF and questionnaires assessing personality, general cognitive ability, and trait EI were administered. The results showed that cold EF affects leadership, emphasizing the mediating role of personality. Furthermore, leaders performed better in communication skills, attention span, and working memory than students.